Survival After Combining Stereotactic Body Radiation Therapy and Tyrosine Kinase Inhibitors in Patients With Metastatic Renal Cell Carcinoma - Liu, Yang; Zhang, Zhiling; Han, Hui; Guo, Shengjie; Liu, Zhuowei; Liu, Mengzhong; Zhou, Fangjian; Dong, Pei; He, Liru (Frontiers in Oncology, 2021)
Background Stereotactic body radiation therapy (SBRT) and tyrosine kinase inhibitors (TKIs) are effective treatments for metastatic renal cell carcinoma, but data on combining these two modalities are scarce. We aimed to investigate the survival outcomes of SBRT plus TKIs. Methods Data of patients treated with TKIs from December 2007 to June 2019 were collected. Patients received SBRT plus TKIs (TKI + SBRT group) or TKIs alone (TKI alone group). Local control (LC), time to change of systemic therapy (TTS), and overall survival (OS) were assessed. Results A total of 190 patients were included, and 85 patients received TKI + SBRT. The 2-year LC rate was 92.8%. The median OS in the TKI + SBRT group was significantly longer than that of the TKI alone group (63.2 vs 29.8 months; P < 0.001). In multivariate analysis, IMDC intermediate (HR 1.96; 95% CI 1.10–3.48; P = 0.022) and poor risk (HR 2.43; 95% CI 1.25–4.75; P = 0.009), oligometastasis (HR 0.41; 95% CI 0.26–0.65; P < 0.001), and the addition of SBRT (HR 0.48; 95% CI 0.31–0.75; P = 0.001) were prognostic factors for OS. Patients with oligometastasis (P = 0.009) and those with IMDC favorable (P = 0.044) or intermediate (P = 0.002) risk had significantly longer OS with TKI + SBRT. The median TTS were 21.5, 6.4, and 9.0 months in patients receiving SBRT before first-line TKI failure, SBRT after first-line TKI failure, and first-line TKI alone (P < 0.001). Five patients (5.9%) experienced SBRT-related grade 3 toxicities. Conclusions Combining SBRT with TKIs is tolerable and associated with longer OS in selected patients, such as those with oligometastasis and favorable or intermediate risk.